Effect of Ethanol Extract of Eleutherine bulbosa (Mill.) URB on Anaerobic Bacterial Prophyromonas gingivalis In Vitro - Siti Nur Azizah; Sinar Yani; Sjarif Ismail; Masyudhi Masyudhi; Endang Sawitri (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2018)
Periodontitis is an inflamation of supporting tissues on teeth that became the main cause of Prophyromonas gingivalis (P. gingivalis) bacteria. Treatment of periodontitis is by giving antibacterial agent therapy. Plants that have antibacterial effects one are Eleutherine bulbosa (UEB) bulbs from the Iridaceae family. This plant has been used for ethnobotany boils drugs and has been known to have antibacterial activity toward against intestinal pathogen bacteria that is anaerobic Gram Negative, but still unknown its activity against on oral pathogenic bacteria such as P. gingivalis. The purpose of this study was to know the effect of UEB extract on the growth of P. gingivalis bacteria as in vitro. UEB is taken from agriculture center in Samarinda city. UEB Simplisia was tested for antibacterial activity using Kirby-Bauer disc diffusion method on BHI-A media supplemented with vitamin K and hemin. The bacteria which used were P. gingivalis ATCCÂ® 33277. Blank disc 6 mm with nine concentrations attached to BHI-A medium, incubated for 24 hours at 37 Â°C in an anaerobic atmosphere, then sprayed MTT (3-[4,5-Dimethylthiazole-2-yl]-2,5-diphenylttetrazoliumbromide) reagent and read a few moments later. For comparison, then used Chlorhexidine gluconate (CHX) 2 mg/ml. The statistical analysis with t-test and there was significant different if p<0.05. The result showed that the higher concentration of UEB ethanol extract will increase the growth inhibition zone of P. gingivalis bacteria and reach maximum at 10 mg/ml concentration. The result of t-test showed no difference significant of P. gingivalis bacterial inhibition zone in the treatment group of 7.5 mg/ml and 10 mg/ml concentration on CHX group. This study proves UEB ethanol extract can inhibit the growth of P. gingivalis bacteria.